Sikap dalam Dilema Etik dan Sikap Profesional Perawat terhadap Kualitas Pelayanan - Cicih Ratna Nengsih; Mulyati Mulyati; Arina Novilla (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to identify the influence of attitudes in ethical dilemmas and professional attitudes of nurses on service quality. The research method used in this research is quantitative research. The study results from the Ethical Dilemma variable were 67.48% with a pretty good category, the Professional Nurse variable was 65.11% with a reasonably good type, and the Service Quality variable was 68.31% with a good enough sort. In conclusion, there is a significant relationship between the attitude of ethical dilemmas to the service quality of Majalengka Hospital and a substantial connection between the professional attitude of nurses to the service quality of Majalengka Hospital. Keywords: Quality of Service, Professional Nurse